2015
DOI: 10.3389/fphys.2015.00207
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis and RNA interference of cockroach phototransduction indicate three opsins and suggest a major role for TRPL channels

Abstract: Our current understanding of insect phototransduction is based on a small number of species, but insects occupy many different visual environments. We created the retinal transcriptome of a nocturnal insect, the cockroach, Periplaneta americana to identify proteins involved in the earliest stages of compound eye phototransduction, and test the hypothesis that different visual environments are reflected in different molecular contributions to function. We assembled five novel mRNAs: two green opsins, one UV ops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 38 publications
5
80
0
Order By: Relevance
“…Opsin losses have occurred in other animals, including the American cockroach ( Periplaneta americana ) 28 , deep sea fish 29 , fossorial snakes 30 , caecilians 31 and both nocturnal and aquatic mammals 3234 . Such losses are typically associated with low-light or spectrally-attenuated environments.…”
Section: Discussionmentioning
confidence: 99%
“…Opsin losses have occurred in other animals, including the American cockroach ( Periplaneta americana ) 28 , deep sea fish 29 , fossorial snakes 30 , caecilians 31 and both nocturnal and aquatic mammals 3234 . Such losses are typically associated with low-light or spectrally-attenuated environments.…”
Section: Discussionmentioning
confidence: 99%
“…However, because RNAi efficacy is variable among insect species (e.g., RNAi experiments were unsuccessful in some studies using Lepidoptera) (Bellés, 2010;Terenius et al, 2011), consideration of the target insect species is required. Previously, RNAi was demonstrated to work well in two cockroach species, P. americana and B. germanica (Cruz et al, 2006;Pueyo et al, 2008;Gomez-Orte & Bellés, 2009;Revuelta et al, 2009;Irles et al, 2013;French et al, 2015;Lozano et al, 2015;Lemonds et al, 2016). For example, the requirement of the melanin pathway for overall body pigmentation in P. americana nymphs and adults was revealed by RNAi of two enzymecoding genes (Lemonds et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis of this unique insect group is expected to greatly contribute to the comparative study of V-ATPases. Additionally, RNAi works well as a powerful reverse genetics tool in two other sanitary pest species, P. americana and B. germanica (Cruz et al, 2006;Pueyo et al, 2008;Gomez-Orte & Bellés, 2009;Revuelta et al, 2009;Irles et al, 2013;French et al, 2015;Lozano et al, 2015;Lemonds et al, 2016). Nevertheless there is no report of RNAi in P. fuliginosa, the most abundant pest cockroach species in Japan (The Japanese Society of Pestology, Personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…A transcriptome study in cockroaches found that trpl was approximately 10 times more abundant than trp (French et al 2015). RNAi of trpl reduced electroretinogram (ERG) response much more than trp after 21 days suggesting that, unlike D. melanogaster, cockroach TRPL rather than TRP has a larger contribution to phototransduction (French et al 2015).…”
Section: Ion Channels Used In Diurnal and Nocturnal Insectsmentioning
confidence: 99%
“…Instead a lepidopteran paralog appears to carry out a similar function of chromophore binding (Macias-Muñoz et al 2017). Moreover, as observed in the cockroach, while genes such as TRP and TRPL are conserved and expressed, one gene copy (TRPL) might have a greater impact on phototransduction than the other (French et al 2015). Consequently, investigating both gene gain/loss and the expression of phototransduction genes in Lepidoptera might uncover differences in their visual processing that helps them function in different light environments.…”
Section: Introductionmentioning
confidence: 99%